Reliability of a 5-m multiple shuttle test - Boddington, M. K.; Lambert, M. I.; Gibson, A. S.; Noakes, T. D. (Journal of Sports Sciences, 2001)
The aim of the present study was to determine the reliability of a modified 5-m multiple shuttle test. The 'match-related fitness' of 23 female hockey players was assessed on four occasions within 4 weeks. The results of each test session and each shuttle were analysed using analysis of variance with repeated measures to determine the reliability of the test. The mean distance for each of the six shuttles decreased (121.2 +/- 7.5, 114.5 +/- 7.5, 112.2 +/- 7.5, 109.9 +/- 7.9, 108.4 +/- 8.1 and 108.7 +/- 8.3 m for shuttles 1-6, respectively; P < 0.001) similarly for each of the four sessions (P = 0.99). The total and peak distances covered during the tests were not significantly different (P = 0.99 and P = 0.12, respectively). The intra-class correlation coefficient (R) for these variables was 0.98 and 0.86, respectively. The delta distance and the fatigue index calculated post-test were significantly different (P = 0.001 and P = 0.006, respectively) between the four sessions. The intra-class correlation coefficient for both these variables was 0.74. Heart rate and rating of perceived exertion (RPE) were not significantly different between sessions (P = 0.42 and P = 0.095, respectively). The intra-class correlation coefficient for heart rate ranged from 0.65 to 0.97 and that for RPE from 0.85 to 0.91. We conclude that the 5-m multiple shuttle run test is a reliable measure of total and peak distances, heart rate and RPE response and is sufficiently reliabile to track changes in fitness over a season. The delta distance and fatigue index are not as reliable and should be interpreted with caution.